Evaluation and economic valorization of the wild fauna in the Algodon River, Peruvian Amazonia - Aquino, Rolando (2007)
This paper reports on habitats, quantitative abundance and economic valorization of the wild fauna inhabiting the Algodon river basin. In this study we determinate the habitats, realized interviews to hunters and censuses along transects. Censuses were carried out in seven of the ten types of the distinguished habitats; 329 direct observations of mammals, birds and reptiles were made in these transects. Among the mammals, the White-lipped Peccary (Tayassu pecari Link) and the Woolly Monkey (Lagothrix lagotricha Humboldt) were the most abundant, with 9,8 individuals/km2, equivalent to 323,4 kg/km2 of biomass, and 18,4 individuals/km2, equivalent to 202,4 kg/km2 of biomass, respectively. In birds, the highest density corresponded to the Spix’s Guan (Penelope jacquacu Spix) with 5,4 individuals/km2, equivalent to 6,9 kg/km2 of biomass. Without taking in account nocturnal species and some diurnal species, we estimate that around 31891 game animals among mammals and birds inhabit in the study area; whose valorization it was estimated in US$ 349374. Among them, 3479 individuals corresponding with four species of ungulates and one of birds, have commercial/ value, while the rest has subsistence/value